The Expression and Role of Hypoxia-induced Factor-1α in Human Tenon's Capsule Fibroblasts under Hypoxia. (4th March 2021) - Qin, Xi; Wu, Keling; Zuo, Chengguo; Lin, Mingkai
ABSTRACT: Purpose: To determine the expression of hypoxia-induced factor-1α (HIF-1α) and its downstream factors in human Tenon's capsule fibroblasts (HTFs) and changes in HTFs biological functions, we explored the role of HIF-1α in HTFs under hypoxia to provide a basis for studying the regulation of HIF-1α in wound healing after glaucoma surgery. Materials and Methods: we established HTFs hypoxia model in vitro, meanwhile the HIF-1α agonist VH298 or inhibitor KC7F2 was added to HTFs, and the normoxia group was used as a control. Western blot, immunofluorescence and ELISA were used to detect the expression of HIF-1α, vascular endothelial growth factor (VEGF), transforming growth factor-β (TGF-β), Smads and collagen I. The proliferation of HTFs was quantified by cell counting kit-8, and cell migration was tested by healing scratch test. Results: HIF-1α protein expression increased under hypoxia, peaked from 4–24 h, and then decreased. The secretion of VEGF and TGF-β increased with prolonged hypoxia time. VH298 and KC7F2 upregulated and downregulated the levels of VEGF and TGF-β, respectively, suggesting that HIF-1α upregulates and downregulates the levels of VEGF and TGF-β in HTFs under hypoxia, respectively. HIF-1α upregulated the proliferation, migration and collagen synthesis of HTFs under hypoxia. Conclusions: Regulating HIF-1α and its downstream factors effectively regulated HTFs proliferation, migration and collagen synthesis. HIF-1α is a promising regulator in the study of wound healing after glaucoma surgery.